A Conceptual Framework of Sustainable Hospitality Supply Chain Management - Xu, X.; Gursoy, D (Routledge, 2015)
In recent years, companies are under increasing pressure from consumers, grassroots and community organizations, governments, and shareholders to develop and practice sustainable business practices. While individual companies’ sustainability efforts are important, a true sustainability can be achieved only if all members of a supply chain participate in sustainable practices. This study proposes a conceptual hospitality supply chain framework that is developed based on a comprehensive review of sustainability literature in hospitality. This study also discusses the antecedents, consequences, actions, evaluation mechanisms, and sustainability practices that can be implemented by all members of the supply chain on three dimensions (environmental, social, and economic) of the sustainable supply chain management in hospitality business following the principles of triple bottom line reporting (3BL) approach. Managerial implications and future research extensions are also discussed.